2015 9th Malaysian Software Engineering Conference (MySEC) 2015
DOI: 10.1109/mysec.2015.7475216
|View full text |Cite
|
Sign up to set email alerts
|

Toward using software metrics as indicator to measure power consumption of mobile application: A case study

Abstract: Battery capacity of mobile devices is a critical issue for developing green mobile applications. Therefore, energy efficiency has become a major concern nowadays for energy restricted embedded system such as smartphones and tablets. In industry, it is a challenge for them to develop an energy efficient product while meeting customer expectation. In previous study, there is lack of method that uses software metrics to measure power consumption of mobile applications. In this paper we have identified several sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We note several experiments, e.g., [ 55 , 56 , 68 , 71 , 103 , 104 , 105 ], that target power consumption but less than 12% of the RUs in our corpus approach the problem in terms of some energy efficiency metric [ 49 , 50 , 65 , 85 ]. It is necessary to move beyond measurements of how much power was consumed, to measurements of how much power was consumed to carry out a specific task.…”
Section: Thematic Analysismentioning
confidence: 99%
“…We note several experiments, e.g., [ 55 , 56 , 68 , 71 , 103 , 104 , 105 ], that target power consumption but less than 12% of the RUs in our corpus approach the problem in terms of some energy efficiency metric [ 49 , 50 , 65 , 85 ]. It is necessary to move beyond measurements of how much power was consumed, to measurements of how much power was consumed to carry out a specific task.…”
Section: Thematic Analysismentioning
confidence: 99%
“…We note several experiments, e.g. [59,60,81,83,[114][115][116] that target power consumption but less than 12% of the RUs in our corpus approach the problem in terms of some energy efficiency metric [57,58,78,97]. It is necessary to move beyond measurements of how much power was consumed, to measurements of how much power was consumed to carry out a specific task.…”
Section: Lack Of Use Of Metrics Of Energy Efficiency and Standards To Address This Deficiencymentioning
confidence: 99%
“…By working closely with the industry representatives, as well as consulting the literature in this field (data and findings revealed in [22][23][24][25][26]), we have come up with the list of metrics that the potential users would find most valuable [27][28][29] (Table 1).…”
Section: -Process Metrics -Project Metrics -Product Metricsmentioning
confidence: 99%
“…It can be followed by better development estimates and more qualified product that can maintain the customers expectations. As it was stated in the paper [25], developers need a set of valid indicators in assisting the developers for better applications. Thus, the study results showed that Cyclomatic complexity, Number of classes, LOC, number of parameters, nested block depth, number of methods, weighted methods per class and method lines have direct relationship with power consumption of mobile applications.…”
Section: -Process Metrics -Project Metrics -Product Metricsmentioning
confidence: 99%